A bibliometric analysis of telerehabilitation services for patients with stroke - Wu, Dan; Zhang, Haojie; Leng, Yan; Li, Kai; Li, Shijue; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2023)
Background Routine rehabilitation services were disrupted by the COVID-19 pandemic outbreak. Telehealth was identified as an alternative means to provide access to these services. This bibliometric study aimed to analyze the scientific literature to discover trends and topics in the potential applications of telerehabilitation for patients with stroke. Methods The Web of Science electronic database was searched to retrieve relevant publications on telerehabilitation. Bibliometric data, including visual knowledge maps of authors, countries, institutions, and references, were analyzed in CiteSpace. Visualization maps were generated in VOSviewer to illustrate recurrent keywords and countries actively involved in this research area. Results The analysis was performed based on 6,787 publications. The number of publications peaked between 2019 and 2021, coinciding with the years of the COVID-19 outbreak. A total of 113 countries in Europe, North America, Asia, and Oceania had at least one publication in this research field, implying global attention in this research area. Nine of the top 10 most productive countries are developed countries, indicating a potentially higher capability to implement a telerehabilitation program. Conclusion The potential benefits and diversity of telerehabilitation are already highly visible from clinical studies, and further improvements in these technologies are expected to enhance functionality and accessibility for patients. More relevant research is encouraged to understand the barriers to increased adaptation of telerehabilitation services, which will finally translate into a significant therapeutic or preventive impact.